(untitled) (Asian Journal of Medical and Biological Research, 2022)
Lysozyme (lyso) is an anti-microbial peptide (AMP) found in Eukaryotes. In shrimps, lysozyme gene is expressed for protection against microbial infection. This current study targeted to determine the differences in expression in the samples from two different coastal regions having spatial variation for comparison. In the current study, diseased shrimps were collected from improved traditional ghers of Satkhira and Cox’s Bazar districts which are two different coastal areas of Bangladesh. Healthy shrimps were also collected from the ghers of those regions. Average relative expression of lyso gene in diseased shrimps from Satkhira region was lower than that of Cox’s Bazar region. Average fold-differences were observed 1.9, 2.3, and 2.5 in the shrimps collected from the ghers of Satkhira, and it was observed 2.6, 2.9 and 2.7 in the shrimp ghers of Cox’s Bazar. This study supports the hypothesis that immune-related gene expression might vary in different farms and regions in variations of water, environment and biological parameters for the state of the host. Asian J. Med. Biol. Res. 2022, 8 (3), 141-145